Winning coalitions in plurality voting democracies - René van den Brink; Dinko Dimitrov; Agnieszka Rusinowska (Social Choice and Welfare, 2020)
We consider plurality voting games being simple games in partition function form such that in every partition there is at least one winning coalition. Such a game is said to be weighted if it is possible to assign weights to the players in such a way that a winning coalition in a partition is always one for which the sum of the weights of its members is maximal over all coalitions in the partition. A plurality game is called decisive if in every partition there is exactly one winning coalition. We show that in general, plurality games need not be weighted, even not when they are decisive. After that, we prove that (i) decisive plurality games with at most four players, (ii) majority games with an arbitrary number of players, and (iii) decisive plurality games that exhibit some kind of symmetry, are weighted. Complete characterizations of the winning coalitions in the corresponding partitions are provided as well.
Keywords: 330; Economic Theory/Quantitative Economics/Mathematical Methods; Public Finance; International Political Economy; Game Theory; Economics; Social and Behav. Sciences; Social Policy